An Organic Cathode Material S‐3Q@MWCNT with Monoelectrochemical Conversion Phase for Highly Reversible Lithium Batteries. Issue 12 (15th December 2021) - He, Zhipeng; Zhang, Jingjing; Guo, Xiumei; Kang, Hai; Wang, Zhihua; Liu, Yilin; Wang, Minghua; Zhang, Hanping
Abstract : Monoelectrochemical Conversions Multielectrochemical phase conversion is usually involved in a fast capacity fading during charge–discharge processes. In article number 2100108 by Minghua Wang, Hanping Zhang, and co‐workers, an organic sulfur material S‐3Q@MWCNT exhibits monoelectrochemical phase conversion with an enhanced cycling performance. The finding that the chemical matching point and the electrochemical matching point are consistent with each other is also presented.